WHO OWNS DEMOCRACY? - Derber, Charles. Link ([S.l.])
1 online resource
Keywords: This book uniquely reverses today's MAGA conspiratorial concept of the deep state to reveal how a very real deeper state is evident throughout history, back to the founding of American democracy. Class and caste-based elites and their political allies have held dominant power in the US. Large corporations, Wall Street, and other sectors of the capitalist class outsource day-to-day governance to the mainstream political parties, which can compete vigorously and create a credible veneer of civil liberties and electoral democracy, disguising and legitimating the deep state. But it is a shallow democracy, since the deep state sets boundaries on policies and choices to serve itself. It also denies a universal franchise and obstructs the voting rights of people of color, the poor, and other communities threatening to the deep state. Moreover, the deep state constrains civic governance in the workplace and community, denying virtually all working people democratic control over their economic and social life. Shallow democracy has a long history. Two embryonic deep states - a Northern capitalist deep state and a Southern slave-based deep state - came together in a tense and unstable union to create and govern the US. While the Confederate deep state, which we call proto-American fascism, was defeated in the Civil War, it left a deep imprint on the culture and politics of millions of Americans, and has resurged again in Trumpism. The shallow democracy of the capitalist deep state has survived previous challenges, but it lacks the deep roots that guarantees its survival. The authors point to prospects for meaningful change arising from the extreme economic chasm dividing the nation economically and racially, and from existential crises of the survival of democracy and of a sustainable planet. They discuss strategy that might finally move the nation beyond MAGA toward deep democracy.